The Policy of the United States of America to Manage the Crisis Kurdish Regions Outside the Administration of the Kurdistan Region After 2003 - Ghanm Karim Mohammed; Musa Mohammed Kaval (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Kurdish regions outside the administration of the Kurdistan region, according to most historical and legal documents, are part of the territory of the Kurdistan Region, according to legal and constitutional procedures. These problems had to be solved before 2007, but to the extent that the problems are stuck between the region and Iraq. Through this research, the researcher endeavored to present the problems and obstacles in Kirkuk and the Kurdish regions through the two doors, in the field and the field. The study touched on the position and policy of the United States of America and successive Iraqi governments after 2003 in dealing with the crisis legally and dysfunctionally, and the presidency reached until. America did not seek to solve the outstanding problems and the Iraqi government did not save Article 58 of the Iraqi constitution in the transitional phase in 2004 and Article 140 of the permanent Iraqi constitution that the Iraqi people voted in 2005 for, did not enter into these matters in any way, America works Provided that these regions have problems and obstacles and try to be these regions as they are not to move to either of them and he is with the joint administration to promote various reconciliation in these areas.